Exploring the N-Curve of CO2 Emissions: The Interactive Roles of Trade, Manufacturing, Financial Development, and Fiscal Policy across Income Groups - Fildzah, Lina Absharina; Liana, Damia; Rafi'i, Rafi'i; Cahyono, Jordan Putra; Sayekti, Azzahra Mubyaring Putri; Mukin, Karolinda Kidi (International Journal of Energy Economics and Policy, 2025)
This study analyses the relationship between trade openness, the manufacturing industry, financial development, and fiscal policy on CO2 emissions using the System-GMM approach in 119 countries from 2008 to 2023, grouped by income level. The results demonstrate a nonlinear relationship, consistent with the EKC hypothesis, characterized by variations in the shape of the curve. Trade openness is significant in low-income countries, characterized by an inverted N-curve pattern, whereas manufacturing and financial development influence high-income groups, exhibiting an N-curve pattern. Fiscal policy is substantial in the upper-middle group, characterized by an inverted N-curve, and forms a U-curve in the combined group of all countries. The interaction between variables reveals differences: Financial development, combined with trade openness, reduces emissions in the overall group, whereas manufacturing actually increases emissions in the low-income group. Effective fiscal policy, on the other hand, reduces emissions in the lower-middle and combined groups. These findings underscore the importance of considering income context and implementing integrated policies to reduce emissions.